Basic Principles Of Pedagogical Strategies For Professional Competence Development In Future Primary Class Teachers Based On Advanced Foreign Experiences (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
During the implementation of the "Uzbekistan-2030" strategy, one of the main issues was the development of primary education [1, p. 4]. It is important to equip future primary school teachers with modern professional competencies in higher pedagogical educational institutions, and it is also important to rely on advanced foreign experiences. In order to use such advanced foreign experiences, it is appropriate to determine the main principles of the current pedagogical strategies. Here we draw your attention to the analysis of this issue. The principle of academic independence of pedagogical strategies